PEDAGOGIK DIZAYN MODELLARI O‘QITUVCHINING INNOVATSION PEDAGOGIK FAOLIYATINING TARKIBIY QISMI SIFATIDA - Atamuratov, R.K. (SCIENCE and SOCIETY, 2024)
The article analyzes the concept of "Instructional design" used in the organization of digital education. Also, the definitions given to this term are differentiated and its models are explained. Recommendations are provided on the design of the educational process in innovative pedagogical activity of the teacher.
Keywords: instructional design; instructional design models; ADDIE model; SAM model; ALD model; Backward model